Women's Experiences of Defecating in the Open: A Qualitative Study. (February 2019) - Abdul Azeez E.P.,; Negi, Dandub Palzor; Mishra, Aditi
The issue of open defecation is ubiquitous in a country like India where certain demographic groups are underprivileged and often the victims of substandard life and human right violations. Women are the direct victims of open defecation and the non-availability of toilets and the practice of open defecation makes women vulnerable to health risks and gender-based violence. The present article analyses the practice of open defecation by conducting in-depth interviews with 30 women in the reproductive age group in the five villages of Bandarsindri, Kheda, Sirohi, Mundoti and Nahoriyain in central Rajasthan. The study found that women's experience of open defecation is accompanied by fear, shame, lack of privacy and dignity, and conflict—all of which impact the overall quality of life.